The effect of water quality, acidification, and zinc source on growth performance of nursery and finishing pigs - Corso, Maxwell Lane (My University, 2024)
This thesis contains three chapters summarizing research: 1) evaluating the effect of zinc sources on growth performance and body weight variation of grow-finish pigs, 2) evaluating water characteristics and their effects on reducing water pH using citric acid, and 3) evaluating the effect of dietary ABC-4 formulation strategy, water source, and water acidification on the growth performance and fecal dry matter of nursery pigs. Chapter 1 utilized 3,159 pigs to determine the effect of zinc (Zn) source on growth, carcass characteristics, and within-pen body weight (BW) and hot carcass weight (HCW) variation in a commercial finishing research setting. Experimental diets contained 100 mg/kg of Zn from Zn hydroxychloride (ZnHyd), zinc sulfate (ZnSO₄), or zinc oxide (ZnO). Overall, there were no differences observed for growth performance or carcass characteristics. Zinc source did not affect BW or HCW variation at first marketing or final marketing. Chapter 2 involved the collection of 45 water samples from swine production sites across six states that were analyzed to determine the effects of their chemical characteristics on pH reduction with citric acid. Analyses included hardness, pH, calcium (Ca), and magnesium (Mg). Based on the findings of this research, water hardness, Ca, Mg, and initial pH cannot fully predict the amount of citric acid required to reach a stable sample pH of 4.0. However, relationships were observed that can partially explain the variation in the amount of acid required. Chapter 3 utilized 987 nursery pigs to determine the effects of dietary ABC-4 formulation strategy, water acidification, and water source on growth performance, and fecal dry matter (DM) of weanling pigs. Treatments included diets formulated to either a low or high acid binding capacity-4 (ABC-4) value, with high ABC-4 diets containing pharmacological levels of ZnO and low ABC-4 diets containing only basal nutritional levels of Zn. Water was supplied from either rural or well sources, with water source being acidified or not. Ultimately, formulating diets with ZnO at pharmacological levels improved ADG and ADFI compared to low ABC-4 diets without pharmacological levels of ZnO, with the main effects of water source and acidification having minor impacts. Fecal dry matter tended to be increased in rural water compared to pigs offered well water, but removals and mortality were not affected. In summary, these experiments provide greater understanding of the effect of zinc source when provided to growing-finishing pigs, the relationship between water quality parameters and the ability to change water pH, and the effect of feed and water acidification on growth performance of nursery pigs.
Keywords: Acidifier; Finishing-pigs; Nursery-pigs; Water; Weight variation; Zinc